Correlation between clinical disease activity and sacroiliac magnetic resonance imaging detection in axial spondyloarthropathy - Ozenc Inan; Ebru Aytekin; Yasemin Pekin Dogan; Ilhan Nahit Mutlu; Kübra Aydemir; Nuran Oz; Nil Sayiner Caglar (Archives of Rheumatology, 2024)
Objectives: The study aimed to evaluate the correlation between the clinical disease activity of axial spondyloarthropathy (axSpA) and magnetic resonance imaging findings of the sacroiliac joint. Patients and methods: Thirty-two patients (21 males, 11 females; mean age: 39.3±9.2 years; range, 18 to 55 years) who were diagnosed with axSpA according to the Assessment in Spondyloarthritis International Society classification criteria between November 2015 and August 2017 were included in this cross-sectional study. Visual Analog Scale (VAS), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS)-erythrocyte sedimentation rate (ESR), and ASDAS-C-reactive protein (CRP) were used as the indicators of clinical activity. Magnetic resonance imaging of the sacroiliac joint was performed and the Spondyloarthritis Research Consortium of Canada (SPARCC) score was evaluated by a radiologist who was blinded to the clinical and laboratory parameters of the patients. Results: The mean duration of symptom onset was 9.3±7.7 years, and the mean duration of diagnosis was 3.6±2.8 years. Human leukocyte antigen (HLA)-B27 was positive in 16 (50%) patients. There was no correlation between the SPARCC score and VAS, BASDAI, MASES, BASFI, ASDAS-CRP, ASDAS-ESR, ESR, and CRP values (p>0.05). In the HLA-B27 subgroup analyses, a statistically significant correlation was found between HLA-B27-negative patients and SPARCC score (r=0.639, p=0.008). Conclusion: No relationship was found between other clinical disease parameters and sacroiliac joint imaging findings, except for the relationship between the SPARCC and BASDAI in HLA-B27- negative patients with axSpA.